Analisis Yuridis Pendampingan Hukum Gugatan Cerai Ghoib Kepada Susanti Binti Ikhsan - Robianti, Masayu (Universitas Sang Bumi Ruwa Jurai, 2025)
Legal aid is provided free of charge to poor people or groups of people. Legal aid providers are legal aid institutions or community organizations that provide legal aid services based on Law no. 16 of 2011 concerning Legal Aid. The organizer of legal aid is the Indonesian Ministry of Human Rights. Poor people have the right to receive legal assistance until the legal problem is resolved and/or the case has permanent legal force, as long as the recipient of the legal assistance concerned does not revoke the power of attorney. The problem approach used for this research is a normative juridical and empirical juridical approach. Data analysis using qualitative juridical analysis. Conclusion Free or free legal aid services in Law Number 16 of 2011 concerning Legal Aid are contained in Article 1 paragraph 2 and Articles paragraphs 1 to paragraph 3. The scope of Legal Assistance also includes legal aid recipients and the basic rights of aid recipients The law is stated in Article 5 paragraph 1 and paragraph 2 of Law Number 16 of 2011. The requirements and implementation mechanism for free legal aid services are in Law Number 16 of 2011. 2011 is regulated in Chapter VI Requirements and Procedures for Providing Legal Aid which are explained in Article 14 paragraph 1 and paragraph 2, Article 15 paragraph 1 to paragraph 5